2019
DOI: 10.5614/j.eng.technol.sci.2019.51.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline-assisted Microwave Pretreatment of Tetraselmis suecica Biomass for Fed-batch Enzymatic Hydrolysis

Abstract: A two-part study on pretreatment and fed-batch enzymatic hydrolysis of pretreated Tetraselmis suecica using a high initial biomass concentration was conducted. First, the effect of different pretreatment processes, i.e. microwave (MC), dilute alkaline (AK), and microwave-alkaline assisted (MAK) pretreatment, on enzymatic hydrolysis of T. suecica biomass was evaluated. Furthermore, high initial biomass concentration enzymatic hydrolysis improvement via a fed-batch strategy was performed. Among the pretreatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It is caused by microwavegenerated microwaves penetrating the lignocellulose wall and directly vibrating molecules, causing an increase in temperature and destroying the lignocellulose structure. These resulting vibrations break inter-and intra-molecular hydrogen bonds, which refers to an increase in the percentage of cellulose [8], [14]. Based on the results of the analysis, the optimum condition in alkaline microwave assisted pretreatment is heating at 95 o C with a contact time in the microwave for 50 minutes.…”
Section: Effect Of Temperature On Alkaline Microwave-assisted Pretrea...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is caused by microwavegenerated microwaves penetrating the lignocellulose wall and directly vibrating molecules, causing an increase in temperature and destroying the lignocellulose structure. These resulting vibrations break inter-and intra-molecular hydrogen bonds, which refers to an increase in the percentage of cellulose [8], [14]. Based on the results of the analysis, the optimum condition in alkaline microwave assisted pretreatment is heating at 95 o C with a contact time in the microwave for 50 minutes.…”
Section: Effect Of Temperature On Alkaline Microwave-assisted Pretrea...mentioning
confidence: 99%
“…Under optimum conditions, alkaline pretreatment produces the highest cellulose content of 64.38% and the smallest lingnin content of 8.13%, while alkaline microwave-assisted pretreatment produces the highest cellulose content of 68.27% and the smallest lingnin content of 6.84%. In addition, according to Kassim et al [8], the delignification process using alkaline pretreatment requires a longer time than alkaline microwave pretreatmentassisted in producing the same cellulose concentration at a fixed alkaline concentration [8], [20].…”
Section: Effect Of Temperature On Alkaline Microwave-assisted Pretrea...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many studies have used RSM optimization for carbohydrate/reducing sugar/extraction from microalgal biomass using autoclaved pretreatment ( Dong et al., 2016 ; Kassim and Bhattacharya, 2016 ). However, MAE of carbohydrate/reducing sugar from microalgal biomass was performed without optimization ( Nur et al., 2016 ; Kassim et al., 2019 ). This indicated that optimization of MAE of carbohydrates using RSM should be employed from microalgal biomass to evaluate the extraction efficiency and subsequently used for bioethanol production.…”
Section: Introductionmentioning
confidence: 99%